Keratoacanthoma: An Underreported Tumor - Rupali Bavikar; Yamini Ingale; Prachi Chouhan; Iqbal Banyameen (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Keratoacanthoma (KA) is a common but underreported tumor of the skin. It is a common cutaneous neoplasm. The most common sites are sun-exposed skin in light-skinned persons of middle age or older. It is considered the prototype of cutaneous pseudo-malignancies. Histopathological verification is done for the diagnosis. The role of radiation therapy and chemical application have not been proven yet. Complete surgical excision is the gold standard for all types of KA.